THE EFFECTIVENESS OF THE CONSUMPTION OF DATES ON THE DURATION OF THE FIRST STAGE OF LABOR IN THE PRIVATELY PRACTICING MIDWIVES OF PEKANBARU CITY - Alyensi, Fatiyani; Weni, Melan (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
Prolonged labor accounts for 5% of the high causes of maternal mortality in Indonesia. It can be caused by inadequate contractions during labor. The purpose of this study was to determine the effectiveness of the consumption of date palm on the duration of the first stage of labor in Privately Independent Midwife Practices of Pekanbaru in January-May 2020. This quasy experiment research used a static group comparison approach. The population was maternity in Dince Safrina Privately Independent Midwife and Afiyah Pratama Clinic in March-April 2020. The total sample of 20 people was taken by purposive sampling technique consisted of 10 women for the experimental group and 10 women for the control group. The method of collecting data was through observation using observation sheets. Data analysis used independent t test with 95% confidence level. The results showed that the average length of labor for mothers who ate dates was 411 minutes (SD = 131.757) and for mothers who did not eat dates was 592 minutes (SD = 212.135). Statistical test results showed that there were differences in the duration of the first stage of labor between mothers who ate dates and those who did not eat dates (p-value = 0.034). It is concluded that the consumption of dates in labor effectively accelerates the first stage of labor. It is recommended for health workers especially midwives to provide education about the benefits of dates in accelerating the delivery of the first stage